Pengaruh Harga dan Lokasi Terhadap Keputusan Pembelian (Studi pada Konsumen Toko Roti Modern Bakery Cukir Jombang) - Lukman Hakim (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
This study aims to determine the effect of Price and Location on Consumer Purchase Decisions at Cukir Jombang Bakery Modern. This study uses quantitative data analysis techniques. This study uses primary data collection techniques obtained from questionnaires. The sample in this study were 30 respondents. Samples were taken using non-probability sampling techniques in the form of incidental sampling, namely the technique of determining samples based on chance, that is, anyone who accidentally met with a researcher could be used as a sample, if viewed by the person who was met by chance it was suitable as a source of data. The data analysis technique uses Multiple Linear Regression. The results showed that: (1) Prices partially have a positive and significant influence on purchasing decisions (2) The location partially has a positive and significant influence on purchasing decisions (3) Prices and locations simultaneously have a positive and significant influence on purchasing decisions in Bakery Modern Cukir Jombang.